PEMILIHAN KARIR MENGGUNAKAN TEORI HOLAND - Cucu Arumsari (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
. Confusion in choosing a major of science, college or work becomes an obstacle to one's success. Therefore it is necessary theory to know how the right way in choosing a career. Holland's theory is one of career theory that explains how to choose a career according to one's personality and everything that goes against it. According to Holland there are six personality types. The Realistic Type, The Investigative Type, The Artistic Type, The Social Type, The Enterprising Type, and the Conventional Type. Based on this career theory,